ISOLATION AND STRUCTURE ELUCIDATION OF ISOQUERCITRIN FROM HYGROPHILA SALICIFOLIA (ACANTHACEAE) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Hygrophila salicifolia is an erect herb (family: Acanthaceae). It has many medicinal uses like diuretic and anti inflammatory in traditional systems of medicine. Till date no data available for its standardisation therefore isolation of phytoconstituent was done from methanolic extract of Hygrophila salicifolia. Besides a known flavonoid, Isoquercitrin was isolated for the first time from a Hygrophila species, namely Hygrophila salicifolia (Acanthaceae). Its structure was established on the basis of its spectroscopic data.